ANALISIS KUALITAS PELAYANAN (WEBSITE SIMPADU-PMI DI UPT P3TKI PROVINSI JAWA TIMUR) - Aprillia Kartika Wulandari; Sri Wahyuni; Sasmito Jati Utama (Faculty of Social and Political Science, 2020)
This study aims to describe and analyze the quality of electronic-based services on the website Sarana Informasi and Pelayanan Terpadu Pekerja Migran Indonesia (simPADU- PMI) in Unit Pelaksana Teknis Pelayanan Penempatan Perlindungan Tenaga Kerja Indonesia (UPT P3TKI) in East Java. This research investigates the level of quality of electronic-based services on the website Sarana Informasi and Pelayanan Terpadu Pekerja Migran Indonesia (simPADU-PMI) in UPT P3TKI in East Java. It uses quantitative descriptive method and data collection techniques are obtained through questionnaires, documentation and interview. Based on the results of the analysis, it can be seen that the level of quality of electronic- based services on the website is still not maximal due to the results between performance and expectations approximately 91,74%. The results of the analysis of the level services quality of the website can be seen based on Importance Performance Analysis (IPA) from three indicators and twenty-three sub indicators obtained an average value of performance appraisal (X) of 3,77 while the assessment of interests (Y) of 4,11. The results of the analysis show that priorities improve service quality on quadrants one and three while in quadrant two and four need to be maintained in supporting the quality of website services in simPADU-PMI.